All-Suture Anchor Settling After Arthroscopic Repair of Small and Medium Rotator Cuff Tears. Issue 14 (December 2019) - Ro, Kyunghan; Rhee, Sung-Min; Kim, Jung Youn; Kim, Myung Seo; Kim, Jong Dae; Lee, Hojin; Rhee, Yong Girl
Background: All-suture anchors are increasingly being used in rotator cuff repair. However, there are debates on the micromotion of all-suture anchors. Purpose: To perform rotator cuff repair on patients with rotator cuff tears and different shoulder bone mineral densities (BMDs) and investigate (1) where the anchor is located under the cortex, (2) if there is any anchor migration settling during follow-up, and (3) if structural outcome differs according to shoulder BMD. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively investigated 88 patients who underwent arthroscopic single-row repair for small- to medium-sized rotator cuff tears (age [mean ± SD], 58.8 ± 7.1 years) from 712 cases of rotator cuff tendon repair between November 2015 and February 2018. Inclusion criteria were as follows: use of an all-suture anchor; preoperative shoulder BMD; and magnetic resonance imaging (MRI) conducted preoperatively, 2 days after surgery, and 10 months after surgery. Patients were excluded from the study if they underwent open rotator cuff repair (n = 118), got surgery with a double-row technique (n = 178), underwent surgery with anchors other than the all-suture type (n = 273), received anchor insertion in sites other than the greater tuberosity owing to concomitant procedures such as biceps tenodesis and subscapularis repair (n = 29), did not take preoperative shoulder BMD (n = 15), had more than a large-size tear (n = 6), and were lost to follow-up (n = 5). After compression of the all-suture anchor during surgery, the strands were pulled multiple times to ensure that the anchor was fixed onto the bone with appropriate tension. BMD was measured before surgery. Depth to anchor (DA), anchor settling, and repaired rotator cuff integrity were measured with MRI. Patients were categorized into 3 groups: group A (BMD, <0.4 g/cm 2 ; n = 31), group B (BMD, 0.4-0.6 g/cm 2 ; n = 32), and group C (BMD, >0.6 g/cm 2 ; n = 25). A total of 65 patients had follow-up MRI. On the basis of rotator cuff tendon integrity, patients were categorized into either a sufficient thickness group (group S, Sugaya classification grade II or lower; n = 44) or an insufficient thickness group (group I, Sugaya classification grade III or higher; n = 21). Results: On time-zero MRI, the DA differed significantly among groups (group A, 3.62 ± 2.02 mm; group B, 5.18 ± 2.13 mm; group C, 6.30 ± 3.34 mm) ( P = .001). The DA was deeper in patients with a higher BMD at time zero ( r = 0.374; P = .001), but the DA did not differ at follow-up MRI (mean, 10.3 months after surgery). On follow-up MRI, anchor settling tended to increase with deeper time-zero DA ( r = 0.769; P < .001). Anchor settling was significantly different among groups (group A, 1.33 ± 1.08 mm; group B, 2.78 ± 1.99 mm; group C, 3.81 ± 2.19 mm) ( P = .001). The proportion of patients with sufficient thickness in each group did not show a statistical difference (group A, 70.8%; group B, 72.7%; group C, 57.9%) ( P = .550). Conclusion: In conclusion, this study confirmed that the postoperative site of anchor insertion in arthroscopic single-row rotator cuff repair with all-suture anchors was located farther from the cortex in patients with higher shoulder BMD and closer to the subcortical bone in patients with lower BMD. On follow-up MRI, no further settling occurred past a certain distance from the cortex, and there was no significant difference in anchor depth or integrity of the rotator cuff tendon based on shoulder BMD. Therefore, minimal settling in the all-suture anchor did not show clinical significance.